Histamine and neuroinflammation: insights from murine experimental autoimmune encephalomyelitis - Passani, Maria Beatrice; Ballerini, Clara (Frontiers in Systems Neuroscience, 2012)
Multiple sclerosis (MS) is a chronic inflammatory, neurodegenerative disease of the CNS whose pathogenesis remains largely unknown, and available therapies are rarely successful in reversing neurological deficits or stopping disease progression. Ongoing studies on MS and the widely used murine model experimental autoimmune encephalomyelitis (EAE) are trying to dissect out the many components of this complex and heterogeneous neurodegenerative disease in the hope of providing a mechanism-based characterization of MS that will afford successful strategies to limit and repair the neuronal damage. Recently, histamine has been postulated to have a key regulatory role in EAE and in MS pathogenesis. Histamine is a mediator of inflammation and immune responses, it explicates its many actions through four G protein-coupled receptors (H1,2,3,4R) that signal through distinct intracellular pathways and have different therapeutic potentials as they vary in expression, distribution of isoforms, signaling properties and function. Immune cells involved in MS/EAE, including dendritic cells and T lymphocytes, express H1R, H2R and H4R, and histamine may have varying and counteracting effects on a particular cell type depending on the receptor subtypes being activated. Here, we review evidence of the complex and controversial role of histamine in MS/EAE pathogenesis and evaluate the therapeutic potential of histaminergic ligands to treat autoimmune diseases.